Silodosin for the treatment of clinical benign prostatic hyperplasia: safety, efficacy, and patient acceptability - Cho, Hee Ju (Dove Medical Press, 2014)
α1-Adrenergic receptor antagonists are commonly used to treat male lower urinary tract symptoms and benign prostatic hyperplasia (BPH). We performed a literature search using PubMed, Medline via Ovid, Embase, and the Cochrane Library databases to identify studies on the treatment of BPH by silodosin. Silodosin is a novel α1-adrenergic receptor antagonist whose affinity for the α1A-adrenergic receptor is greater than that for the α1B-adrenergic receptor. Therefore, silodosin does not increase the incidence of blood pressure-related side effects, which may result from the inhibition of the α1B-adrenergic receptor. Patients receiving silodosin at a daily dose of 8 mg showed a significant improvement in the International Prostate Symptom Score and maximum urinary flow rate compared with those receiving a placebo. Silodosin also improved both storage and voiding symptoms, indicating that silodosin is effective, even during early phases of BPH treatment. Follow-up extension studies performed in the United States, Europe, and Asia demonstrated its long-term safety and efficacy. In the European study, silodosin significantly reduced nocturia compared to the placebo. Although retrograde or abnormal ejaculation was the most commonly reported symptom in these studies, only a few patients discontinued treatment. The incidence of adverse cardiovascular events was also very low. Evidence showing solid efficacy and cardiovascular safety profiles of silodosin will provide a good solution for the treatment of lower urinary tract symptoms associated with BPH in an increasingly aging society.